VAGINISMUS SEBAGAI ALASAN PERCERAIAN MENURUT KOMPILASI HUKUM ISLAM DAN FIQH SYAFI’IYAH - Nurhayati Zein (Marwah: Jurnal Perempuan, Agama dan Jender, 2012)
Vaginismus is a disease or disparity in the form of muscle spastic around vagina mouth, resulting the vagina closed so that it is possible to do sexual intercourse. This article discusses, can vaginismus as the reason for divorce. There is no direct mention in Fikih Syafi'yah and in the Compilation of Islamic Law that virginismus can be as a reason for divorce. Both only satate that one of the reason for divorce is if one gets handicap or disease so that cannot do the duty as wife or husband. Marriage is a tying claiming the existence of execution of rights and obligations between wife and husband. The wife who has virginismus can not do her duty to do sexual intercourse with the husband. Thereby, vaginismus can be take as a reason for divorce.